Efforts to Reduce the Temperature of the Coolant in the Radiator with PCM - Suhartoyo (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to determine the effect of using PCM in reducing the temperature of the water entering the radiator from the engine. Two types of PCM used are made of aluminum and ST 37 steel. They are made like a box measuring 8 cm x 8 cm with a thickness of 2 mm, the center hole is 3.5 cm in diameter, totaling eight pieces. The Machine used is L 300 Colt engine. The results of the study explained that the decrease in engine temperature after using PCM reached 17.50C. While the use of PCM is very effective where the water coming out of the machine can be reduced by 17,830C. Engine speed at stationary conditions (800 rpm – 1100 rpm) aluminum PCM is more effective, but at engine speed starting (1250 rpm – 2000 rpm), the effective PCM is ST 37 steel.